Early results from the ENGAGE registry: real-world performance of the Endurant Stent Graft for Endovascular AAA repair in 1262 patients - Stokmans, Rutger Adriaan; Böckler, Dittmar (European journal of vascular and endovascular surgery, 2012)
Objective The ENGAGE registry was undertaken to examine the real-world outcome after endovascular abdominal aortic aneurysm (AAA) repair (EVAR) with the Endurant Stent Graft in a large, contemporary, global series of patients. Methods From March 2009 to April 2011, 1262 AAA patients (89.6% men; mean age 73.1 years, range 43-93 years) were enrolled from 79 sites in 30 countries and treated with Endurant. Results are described following the reporting standards for EVAR. Follow-up data were tabulated for all 1262 patients at a 30-day follow-up and for the first 500 patients at a 1-year follow-up. Results Intra-operative technical success was achieved in 99.0% of cases. Within 30 days, adverse events were reported in 3.9% of patients, including a 1.3% mortality rate. Type-I or -III endoleaks were identified in 1.5% of cases. Estimated overall survival, aneurysm-related survival and freedom from secondary interventions at 1 year were 91.6%, 98.6% and 95.1%, respectively. At 1 year, aneurysm size increased ≥5 mm in 2.8% and decreased ≥5 mm in 41.3% of cases. Conclusion Early results from this real world, global experience are promising and indicate that endovascular AAA repair with the Endurant Stent Graft is safe and effective across different geographies and standards of practice. Longer-term follow-up is necessary to assess durability of these results.
Gesehen am 27.08.2020